2008
DOI: 10.1051/0004-6361:200811089
|View full text |Cite
|
Sign up to set email alerts
|

Metal enrichment of the neutral gas of blue compact dwarf galaxies: the compelling case of Pox 36

Abstract: Context. Evidence has grown over the past few years that the neutral phase of blue compact dwarf (BCD) galaxies may be metaldeficient as compared to the ionized gas of their H ii regions. These results have strong implications for our understanding of the chemical evolution of galaxies, and it is essential to strengthen the method, as well as to find possible explanations. Aims. We present the analysis of the interstellar spectrum of Pox 36 with the Far Ultraviolet Spectroscopic Explorer (FUSE). Pox 36 was sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 95 publications
3
37
0
Order By: Relevance
“…2.4), and it is lower than the metallicity in the disk, the HI is likely cosmic gas being accreted. Lebouteiller et al (2009) find an even larger discrepancy between the HI and HII metallicities of Pox 36, where the HI metallicity is around 0.03 Z .…”
Section: Neutral Gas Observationsmentioning
confidence: 78%
“…2.4), and it is lower than the metallicity in the disk, the HI is likely cosmic gas being accreted. Lebouteiller et al (2009) find an even larger discrepancy between the HI and HII metallicities of Pox 36, where the HI metallicity is around 0.03 Z .…”
Section: Neutral Gas Observationsmentioning
confidence: 78%
“…When computing M Z,gas , we assume the same metal abundance for the neutral and ionized gas phases. This can be false, as the former may be characterized by lower (by a factor of ∼7, Lebouteiller et al 2009) abundances than the latter. However, this effect does not change our results.…”
Section: Resultsmentioning
confidence: 99%
“…Since we use the information from all available lines in the wavelength range, the error bar can be significantly smaller than when considering a single line. We refer to L04 and Lebouteiller et al (2006Lebouteiller et al ( , 2009) for more details. The comparison between the column densities we derive and the FUSE results asks for caution.…”
Section: Heavy Elementsmentioning
confidence: 99%
“…The neutral gas chemical composition was derived in several BCDs, spanning a wide range in ionized gas metallicity, from 1/30 to 1/3 Z , with I Zw 18 (Aloisi et al 2003, hereafter A03; Lecavelier des Etangs et al 2004, hereafter L04), SBS 0335-052 , I Zw 36 (Lebouteiller et al 2004), Pox 36 (Lebouteiller et al 2009), Mark 59 (Thuan et al 2002), NGC 625 (Cannon et al 2005), and NGC 1705 (Heckman et al 2001;Lee & Skillman 2004). These investigations showed that the neutral gas of BCDs is not pristine; it has already been enriched with metals, with a minimal metallicity of ∼1/50 Z (see the FUSE sample analysis in Lebouteiller et al 2009). The second most important result is that the metallicity of the neutral gas is generally lower than that of the ionized gas − except for the two lowest-metallicity BCDs, I Zw 18 and SBS 0335-052E − implying that the H  region has been probably less processed than the H  region.…”
Section: Introductionmentioning
confidence: 99%